Supply chain risk mitigation in halal product MSMEs using the house of risk approach - Fita Rohmatussholihah; Isdiana Suprapti; Resti Prastika Destiarni; Andi Patiware Metaragakusuma (Journal of Halal Science and Research, 2026)
Implementing halal product assurance policies requires MSMEs not only to verify the halal status of ingredients but also to manage risks across their supply chains. The complexity of activities such as planning, procurement, production, distribution, and product returns can disrupt operations and affect the quality and sustainability of the business. This study aims to identify supply chain risks in halal product MSMEs and formulate mitigation strategies using the House of Risk (HOR) method. Primary data were obtained through observation, interviews, and questionnaires. The analysis results show 21 risk events and 23 risk agents, with three priority mitigation strategies focused on strengthening internal controls, standardizing operational procedures, and increasing supervision. These findings emphasize the importance of a systematic risk management approach in supporting the stability and competitiveness of halal product MSMEs.Keywords: Chili sauce industry, Halal MSMEs, House of risk, Risk mitigation strategy, Supply chain.